Kesenjangan Generasi terhadap Anti-Freud Awareness - Ghina Adhha Haura; Nurliza Lubis (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
This research is a idea of novelty which aims to empirically test about generation gap there is generation X, Y/Milenial, generation Z and Boomers toward anti-fraud awareness which was analyzed with seven variables, there is tone of the top, anti-fraud training, implementation of code of conduct, hotline/whistleblowing system, segregation of duties, fraud risk assessment and background checks. The data source was obtained from distributing questionnaires to individuals in the educational environment. Sampling was carried out at random or simple random sampling. The analytical method used is the Mann-Whitney test with SPSS 25. The research results show that there is a generation gap between generations X and Y, generations X and Z and generations Y and Z. Meanwhile for Generation X and Boomers, generation Y and Boomers as well as generation Z and Boomers do not show a generation gap to raise awareness about the importance of fraud prevention. The limitations of the research are the respondents, especially the Boomer generation respondents. So that further research can increase the number of respondents and in a different scope. It is hoped that this research will provide benefits for determining strategies for anti-fraud awareness according to the character of each generation.